Die Debatte über Deutschlands Umgang mit China: Versuch einer Einordnung - Pils, Eva; Weber, Ralph (Leviathan, 2024)
Germany has been discussing its relation to the People’s Republic of China and its party rule for a while. Based on the German government’s China strategy, we ask for a framework of analysis and evaluation. We criticize the failure to recognize transnational realities, demand a much clearer foregrounding of normative tensions and emphasize the duties limiting state actors’ strategic options for action in a liberal democracy.
CRIS-Team Scopus Importer:2024-10-18
Keywords: autocracy; China; human rights; openness; resilience; transnationality